Landscape differentiation and trends in climatogenic dynamics of ecological regimes within ecotopes of upland oak forests in the southern part of the Left-Bank Forest-Steppe of Ukraine - Бондарук , М. А.; Целіщев , О. Г. (Forestry and Forest Melioration, 2023)
Introduction In the second half of the 21st century, a significant warming and aridization of climatic conditions is expected in Ukraine. The system of research on the specifics and trends of climatogenic dynamics of ecological regimes in forests should include monitoring of climatic and edaphic regimes of ecotopes of forest ecosystems at the local and regional organizational levels. The aim of the study was to make synphyto-indicative assessment of trends in the dynamics of indicators of edaphic and climatic regimes of oak forest ecotopes at the landscape level in accordance with the predicted change in climatic conditions on the example of a model site to monitor the impact of climate change on forest ecosystems in the region. Materials and Methods The research was conducted on 270 monitoring plots within 24 subcompartments of naturally originated middle-aged and premature oak stands in dry, fresh, and wet maple-linden oakery within the model forest massif "Veliky Lis". The plots were evaluated according to their belonging to the elements of landscape-territorial complexes, macrorelief and mesorelief, with the determination of the exposure and steepness of the slopes. The geobotanical description included species of trees, shrubs, and herbaceous plants which were estimated on their abundance-coverage (%) according to the combined scale of G. M. Vysotsky and D. V. Vorobyov. The method of phytoindication of leading factors according to unified scales of ecological amplitudes for flora species in Ukraine (Didukh, 2011) was used for the synphytoindicative assessment of forest ecosystems’ edaphotopes. The analysis of patterns in changes in certain ecological factors and their differentiation at the forest typological and landscape organizational levels included the calculation of хmin, and хmax values of ecological regimes by types of forest conditions that are associated with relief elements. By calculating the correlation coefficients between ecological regimes, the groups of environmental factors were determined, which change synchronously in space and determine the ecological specificity in trends of climatic changes within the ecotopes of upland oak forests. Results It was established that the nature of the differentiation of indicators of the main ecological factors in the ecotopes of upland oak forests in the southern part of the Left-Bank Forest-Steppe under conditions of automorphic nutrition is determined by the contrasts in locations at the level of landscape areas depending on the hypsometric level, the features of the mesorelief of individual plots, in particular, the difference in steepness (from 0 to 15°) and exposure of the slopes, as well as the specifics of the structure of forest communities of different forest types. According to the ordination matrix of correlations between ecological factors, the patterns of the dynamics of ecological regimes within the ecotopes of upland oak forests under the global trend of climate aridization were determined. Along with an increase in the heat amount that enters 1 cm2 per year, a decrease in the winter’s severity and an increase in the microclimate continentality, an increase of moisture evaporation and a decrease of humidity will be observed. In turn, it will lead to a decrease of moisture and mineral nitrogen content in the soil, an increase of alkalinity, a content of carbonates and the level of soil aeration, as well as a slight increase in soil mineralization with non-toxic hydrocarbonate salts. Changes in ecological regimes will take place alternately from the upper levels (tops and upper parts of the slopes of the southern and southeastern exposures) of the ravine-valley areas to the lower levels of the sloping riverine areas of the northern exposure. Conclusions The synphyto-indicative assessment of ecological regimes allows solving crucial issues regarding the complex and economic determination at the local and regional levels of both the current state of ecotopes of forest ecosystems and the specifics of trends in their chronological dynamics under the influence of climate changes, which is an important component of forest monitoring in the post-war period of forestry development. 3 Tables, 28 Refs.